Length-frequency distribution of the eatable cockle, Cerastoderma edule from the Wadden Sea National Park Lower Saxony - Jürgen Laudien; Bo Janßen; Ruben Lietzau; Samir Nasher Taher; Iwo Schulz (PANGAEA, 2018)
Length-frequency distribution of the eatable cockle are analysed betwenn October 2017 and March 2018 in the Wadden Sea National Park Lower Saxony. In addition organic content from the sediments are analysed.